Chronic disease burden predicts food insecurity among older adults - Jih, Jane (Public Health Nutr, 2018)
OBJECTIVE: Increased out-of-pocket health-care expenditures may exert budget pressure on low-income households that leads to food insecurity. The objective of the present study was to examine whether older adults with higher chronic disease burden are at increased risk of food insecurity. DESIGN: Secondary analysis of the 2013 Health and Retirement Study (HRS) Health Care and Nutrition Study (HCNS) linked to the 2012 nationally representative HRS. SETTING: USA. SUBJECTS: Respondents of the 2013 HRS HCNS with household incomes <300 % of the federal poverty line (n 3552). Chronic disease burden was categorized by number of concurrent chronic conditions (0–1, 2–4, ≥5 conditions), with multiple chronic conditions (MCC) defined as ≥2 conditions. RESULTS: The prevalence of food insecurity was 27·8 %. Compared with those having 0–1 conditions, respondents with MCC were significantly more likely to report food insecurity, with the adjusted odds ratio for those with 2–4 conditions being 2·12 (95 % CI 1·45, 3·09) and for those with ≥5 conditions being 3·64 (95 % CI 2·47, 5·37). CONCLUSIONS: A heavy chronic disease burden likely exerts substantial pressure on the household budgets of older adults, creating an increased risk for food insecurity. Given the high prevalence of food insecurity among older adults, screening those with MCC for food insecurity in the clinical setting may be warranted in order to refer to community food resources.